PERAN SIMBOL DALAM LITURGI DAN MANFAAT BAGI PENGHAYATAN IMAN - Uweubun, Yoppi R. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2014)
There is no Christian life without liturgy. Through liturgical activities, the faithful want to express their faith in God‟s saving presence through Jesus Christ. By his death and resurrection, Jesus Christ fulfilled God‟s design of salvation of human mankind. This work of salvation in Jesus Christ is now continued through liturgical celebrations; this is actualized by means of symbols. That means: God‟s saving activity, which is implemented in Jesus and which is celebrated in the liturgy, can only be understood and experienced, when it is being celebrated by means of symbols. Thus in liturgy, symbols play an important part; because it is from there that we can fully understand and experience all that is celebrated in the liturgy itself.